Self-esteem, anxiety and coping strategies to manage stress in ice hockey - Adriana Kaplánová (Palacký University Olomouc, 2019)
Background: Sweating, increased heart rate, fidgeting, worrying thoughts and fear of failure are typical symptoms of an inability to manage stress in an important moment of match. Thus, there is well-founded need for psychological training that can help ice hockey players to control their emotions in stressful situations. Objective: Because of a lack of research monitoring mental skills of ice hockey players, the aim of the study is to investigate the relationship between self-esteem, anxiety of ice hockey players and their coping strategies to manage stress. Methods: The study sample consisted of 40 male ice hockey players with age of 21.67 ± 1.94 years. The level of self-esteem was evaluated by the Rosenberg Self-Esteem Scale RSES, anxiety was measured by the Sport Anxiety Scale SAS-2, and coping strategies to manage stress were assessed by the Athletic Coping Skills Inventory ACSI-28. The study used the correlational research design with Spearman correlation coefficient. Results: We found that coping strategies to manage stress have significant relationship with at least one anxiety construct of the ice hockey players, namely coping with adversity, coachability, concentration, goal setting and mental preparation, peaking under pressure and freedom from worry. We also found that coping strategies to manage stress have significant relationship with the self-esteem of ice hockey players, namely coping with adversity, concentration and freedom from worry. Conclusion: Our research showed that the level of coping strategies to manage stress varies according to the level of self-esteem and the level of the anxiety. It seems that reduced anxiety and increased self-esteem can lead to better stress management and optimal competition performance.